Rapid graphs with tableau 8 : the original guide for the accidental analyst - McDaniel, Stephen; McDaniel, Eileen (Apress Imprint: Apress, 2013)
Tired of boring spreadsheets and data overload from confusing graphs? Master the art of visualization with Rapid Graphs with Tableau 8! Tableau insiders Stephen and Eileen McDaniel expertly provide a hands-on case study approach and more than 225 illustrations that will teach you how to quickly explore and understand your data to make informed decisions in a wide variety of real-world situations. Rapid Graphs with Tableau 8 includes best practices of visual analytics for ideas on how to communicate your findings with audience-friendly graphs, tables and maps. "A picture is worth a thousand words" is a common saying that is more relevant today than ever as data volumes grow and the need for easy access to answers becomes more critical. This book covers the core of Tableau capabilities in easy-to-follow examples, updated and expanded for Version 8. Learn how to be successful with Tableau from the team that started the original training program as the founding Tableau Education Partner! "A must read for anyone interested in Tableau. Clear explanations, practical advice and beautiful examples!" Elissa Fink - Chief Marketing Officer, Tableau Software